The open body: a “new” book - Manzoli, Lucia; Billi, Anna Maria; Falconi, Mirella; Cocco, Lucio (Italian Journal of Anatomy and Embryology, 2017)
At the beginning of the ‘300, Mondino de’ Liuzzi, a physician from Bologna, was the first anatomist who started again the dissection of human body neglected from the III century. He hinted at the existence of the conflict between book and body, between “auctoritas” and the direct observation of the human body . The Mondino’s masterwork “Anothomia” remained the key book up to the middle of the sixth century, when Andrea Vesalio wrote “De Umani Corporis Fabrica,” in which the body (cadaver) eventually became the main player of the book . During the years, the technologic evolution led to the wrong conviction that dissection could be dismissed, albeit, still in our day, doctors in training feel the need to associate the direct experience on the cadaver with the very valuable digital means and the modern imaging technologies even in 3D. Thinking to Anatomy as an already fully well known discipline is a mistake. The most advanced methodologies for surgical access, namely the minimally invasive surgery, require the evolution of the traditional anatomical knowledge. The Human Anatomy Institute of the University of Bologna, among the first in Italy, has recognized this need. Thanks to the generosity of the people enrolled in the Body donation programme for research and teaching, our Institute allows medical students to practice dissection on cadavers, beginning as Freshman, then Sophomore, Junior and Senior. The sharing of Bologna’s experience could be the chance to think about the perspectives offered by the dissection of the corpse: a wide range of possibilities spanning from research projects to advanced training courses in collaboration with clinicians and surgeons belonging to different branches. Moreover the practice of corpse dissection is extremely important for the recruitment of young graduates in Medicine which, by means of the experience vested acting as “tutor of anatomy”, acquire interest in the field of research of morphological sciences, spanning from macroscopic up to the cellular and molecular level. Hic mors gaudet succurrere vitae: the motto, reported in dissection room of most of the Italian anatomical institutes, represents the synthesis of the experience of an ancient discipline which, nowadays , has the chance to rewrite a new chapter dedicated to modern frontiers of scientific research and medical education.